Targeted protein degradation combined with PET imaging reveals the role of host PD-L1 in determining anti-PD-1 therapy efficacy - Du, Jinhong; Han, Shu; Zhou, Haoyi; Wang, Jianze; Wang, Feng; Zhao, Meixin; Song, Rui; Li, Kui; Zhu, Hua; Zhang, Weifang; Yang, Zhi; Liu, Zhaofei (European journal of nuclear medicine and molecular imaging, 2024)
Purpose Immunohistochemical staining of programmed death-ligand 1 (PD-L1) in tumor biopsies acquired through invasive procedures is routinely employed in clinical practice to identify patients who are most likely to benefit from anti-programmed cell death protein 1 (PD-1) therapy. Nevertheless, PD-L1 expression is observed in various cellular subsets within tumors and their microenvironments, including tumor cells, dendritic cells, and macrophages. The impact of PD-L1 expression across these different cell types on the responsiveness to anti-PD-1 treatment is yet to be fully understood. Methods We synthesized polymer-based lysosome-targeting chimeras (LYTACs) that incorporate both PD-L1-targeting motifs and liver cell-specific asialoglycoprotein receptor (ASGPR) recognition elements. Small-animal positron emission tomography (PET) imaging of PD-L1 expression was also conducted using a PD-L1-specific radiotracer 89 Zr-αPD-L1/Fab. Results The PD-L1 LYTAC platform was capable of specifically degrading PD-L1 expressed on liver cancer cells through the lysosomal degradation pathway via ASGPR without impacting the PD-L1 expression on host cells. When coupled with whole-body PD-L1 PET imaging, our studies revealed that host cell PD-L1, rather than tumor cell PD-L1, is pivotal in the antitumor response to anti-PD-1 therapy in a mouse model of liver cancer. Conclusion The LYTAC strategy, enhanced by PET imaging, has the potential to surmount the limitations of knockout mouse models and to provide a versatile approach for the selective degradation of target proteins in vivo. This could significantly aid in the investigation of the roles and mechanisms of protein functions associated with specific cell subsets in living subjects.